Optimal verification strategies in multi‐firm projects. Issue 3 (22nd February 2022) - Kulkarni, Aditya U.; Salado, Alejandro; Wernz, Christian
Abstract: Verification activities are intended to reduce the costs of system development by identifying design errors before deploying the system. However, subcontractors in multifirm projects are motivated to implement locally cost‐effective verification strategies over verification strategies that benefit the main contractor. Incentivizing verification activities is one mechanism by which the contractor can motivate subcontractors to implement verification strategies desirable to the contractor. Prior work on mathematical models of verification in systems engineering has neither explored optimal verification strategies nor incentives in multi‐firm projects. In this paper, we present a modeling concept for determining optimal verification strategies in multi‐firm projects. Our models are belief‐based, which means that contractors and subcontractors incorporate their at times limited knowledge about true verification state through a probabilistic assessment of possible states. We develop an initial two‐level model, where one contractor directly works with multiple subcontractors at the next lower level. This model is then extended to a general network model with multiple, multilevel contractor‐subcontractor relationship. We derive solution algorithms that characterize the optimal verification strategies and incentives for each of the firms. Our work contributes to the systems engineering literature by laying the foundation for the study of incentives as a mechanism to align verification activities in multi‐firm systems engineering projects.